1984
DOI: 10.1093/jac/13.suppl_b.89
|View full text |Cite
|
Sign up to set email alerts
|

Norfloxacin versus cotrimoxazole in the treatment of uncomplicated urinary tract infections--a multi-centre trial

Abstract: One hundred and twenty-two patients with uncomplicated urinary tract infections were treated with either 400 mg bd norfloxacin or 160/800 mg bd cotrimoxazole for 7 days. Follow-up examinations showed norfloxacin to be equally effective as cotrimoxazole in the eradication of bacteriuria and symptoms. Norfloxacin caused fewer and less severe side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…In each comparative study the adverse effects reported with norfloxacin were similar to (14,16,18,19,28,(34)(35)(36)40) (11,14,16,18,19,25,27,28,(34)(35)(36)40). Gastrointestinal symptoms (nausea, vomiting, anorexia) and central nervous system symptoms (lightheadedness, headache, drowsiness, insomnia) were the most frequently reported but rarely were severe or required cessation of therapy.…”
Section: Toxicities Of the Fluoroquinolones In Humansmentioning
confidence: 75%
See 3 more Smart Citations
“…In each comparative study the adverse effects reported with norfloxacin were similar to (14,16,18,19,28,(34)(35)(36)40) (11,14,16,18,19,25,27,28,(34)(35)(36)40). Gastrointestinal symptoms (nausea, vomiting, anorexia) and central nervous system symptoms (lightheadedness, headache, drowsiness, insomnia) were the most frequently reported but rarely were severe or required cessation of therapy.…”
Section: Toxicities Of the Fluoroquinolones In Humansmentioning
confidence: 75%
“…In the presence of meningeal inflammation, pefloxacin appears to penetrate well into the cerebrospinal fluid, reaching concentrations of 4.8 ± 0.79 ,ug/ml (44% that of serum) (47). Similar drug penetration into cerebrospinal fluid was also seen when pefloxacin was given after the recovery of patients from meningitis (47 [34][35][36]40). Norfloxacin, when given with one exception (14) in doses of 400 mg orally twice daily, demonstratqd significantly higher (35,36) or equivalent rates of cure when compared in eight randomized, nonblinded studies to orally administered trimethoprim-sulfamethoxazole (14,16,18,19,36,40), amoxicillin (28), or nalidixic acid (35) ( Table 2).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…[8][9][10] Serious side effects from norfloxacin included severe gastrointestinal effects and central nervous system effects. 8,[20][21][22] Costs. From a societal perspective, the data on direct medical costs in 1999 U.S. dollars (Table 2) were collected, including costs of antibiotic therapies, treating adverse reactions from antibiotics, inpatient treatment, ED visits, and office visits.…”
Section: Study Setting and Populationmentioning
confidence: 99%